2018
DOI: 10.1101/437236
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cytoskeletal tension actively sustains the migratory T cell synaptic contact

Abstract: When migratory T cells encounter antigen presenting cells (APCs), they arrest and form radially symmetric, stable intercellular junctions termed immunological synapses which facilitate exchange of crucial biochemical information and are critical for T cell immunity. While the cellular processes underlying synapse formation have been well-characterized, those that maintain the symmetry, and thereby the stability of the synapse remain unknown. Here we identify an antigen-triggered mechanism that actively promote… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 81 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…2A-B) The similarity in WASP-/-and WASPΔC CTL phenotypes indicated that WASP's nucleation-promoting factor (NPF) activity is essential for its support of TCR activation and CTL cytotoxicity. To further test whether the mechanical stresses are compromised in WASP-/-CTL synapses, we utilized the lymphocyte form of P130Cas (CasL), phosphorylated at Tyr-249, as endogenous mechanotransduction sensor 30 . P130 Cas as well as CasL localize to filamentous actin and show higher phosphorylation at Tyr-249 in response to elevated local cytoskeletal stresses 30,45,49 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2A-B) The similarity in WASP-/-and WASPΔC CTL phenotypes indicated that WASP's nucleation-promoting factor (NPF) activity is essential for its support of TCR activation and CTL cytotoxicity. To further test whether the mechanical stresses are compromised in WASP-/-CTL synapses, we utilized the lymphocyte form of P130Cas (CasL), phosphorylated at Tyr-249, as endogenous mechanotransduction sensor 30 . P130 Cas as well as CasL localize to filamentous actin and show higher phosphorylation at Tyr-249 in response to elevated local cytoskeletal stresses 30,45,49 .…”
Section: Resultsmentioning
confidence: 99%
“…To further test whether the mechanical stresses are compromised in WASP-/-CTL synapses, we utilized the lymphocyte form of P130Cas (CasL), phosphorylated at Tyr-249, as endogenous mechanotransduction sensor 30 . P130 Cas as well as CasL localize to filamentous actin and show higher phosphorylation at Tyr-249 in response to elevated local cytoskeletal stresses 30,45,49 . Indeed, phospho-Tyr-249-CasL (pCasL) was reduced in the synapses formed between B16 and WASP-/-CTL and could be significantly rescued by the expression of full-length WASP protein.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations